SAT0224 Amelioration of inflammatory disease activity and vascular inflammation with hmg-coa reductase inhibition and angiotensin receptor blockade in rheumatoid arthritis. (12th June 2018) - Syngle, A.; Garg, N.; Krishan, P.
Abstract : Background: Rheumatoid Arthritis (RA) has 50% increased risk of cardiovascular (CV) mortality 1 . Similarities between atherosclerosis and RA and proven benefit of Angiotensin receptor Blockers and HMG-CoA reductase inhibitors in atherosclerotic vascular disease provide strong rationale to investigate the impact of Rosuvastatin, HMG-CoA reductase inhibitor and Olmesartan, an angiotensin receptor blocker on inflammatory disease activity and vascular inflammation in RA. Objectives: To investigate the impact of Rosuvastatin and Olmesartan on inflammatory disease activity and vascular inflammation in RA Methods: 84 RA patients randomized to 3 groups to receive 24 weeks of treatment with Rosuvastatin (Rvs) (10 mg/day, n=28), Olmesartan (OLME) (10 mg/day, n=28) and placebo (PL) (n=28) as an adjunct to existing stable antirheumatic drugs. 2 patients from the OLME group were lost to follow up. FMD was assessed by AngioDefender. EPCs were estimated by flow cytometry. Measures of vascular inflammation: serum nitrite, TBARS, adhesion molecules (ICAM-1 and VCAM-1) and lipids were measured at baseline and after treatment. In&xFB02;ammatory measures included DAS28, SDAI, CRP and ESR, pro-inflammatory cytokines (TNF-α, IL-6 and IL-1). SCORE system estimated the 10 year risk of a first fatal atherosclerotic event. Quality of life was assessed with HAQ-DI and SF-36. Results: At baseline, FMD correlated inversely with DAS28 (r= -0.42, p<0.05) and TNF- α (r= -0.50, p<0.05) and positively correlated with EPCs (r= 0.44, p<0.05) in all three groups indicating high inflammatory disease activity and decreased EPCs population associated with endothelial dysfunction. FMD also correlated inversely with CRP in both Rvs (r= -0.46, p<0.05) and OLME (r= -0.40, p<0.05) groups. After treatment, FMD improved significantly in the Rvs vs. OLME vs. PL group from their baseline levels, respectively Rvs vs. PL (p<0.01), OLME vs. PL (p≤0.01), Rvs vs. OLME (p=0.03) (Fig.1A). The improvement in FMD after treatment with Rvs was significantly greater than OLME [Rvs vs. OLME (p=0.03)]. EPCs and nitrite levels were improved significantly in both Rvs and OLME groups. A significant reduction was found in ICAM-1 after Rvs treatment (p<0.01) where as OLME significantly decreased VCAM-1 and TBARs (p=0.04), (p=0.01) respectively. Both Rvs and OLME resulted in significant reductions of DAS28 (figure 1B), SDAI, ESR, CRP (figure 1C), IL-6 and TNF-α (figure 1D) vs. PL. There was a significant reduction in the SCORE, HAQ-DI and SF-36 score after treatment with Rvs and OLME. Conclusions: Rvs and OLME ameliorate inflammatory disease activity and vascular inflammation in RA. Both Rvs and OLME lowers the TNF-α & IL-6 which down regulates the production of CRP and NO and improved EPC population and FMD. However, Rvs also favourably impacted ICAM-1 and lipid abnormalities while OLME has beneficial effect on VCAM-1, TBARs and blood pressure. Thus, both Rvs and OLME ameliorate inflammatory disease activity, reduce cardiovascular risk in context of vascular inflammation, endothelial dysfunction and EPCs biology. Reference: 1López-Mejías R, Castañeda C, González-Juanatey C, et al. Autoimmunity Reviews2016;15:1013–1030. Disclosure of Interest: None declared